1988
DOI: 10.1111/j.1911-3846.1988.tb00706.x
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of financial distress prediction models to departures from normality*

Abstract: Abstract. This research empirically investigated the effect of nonnormality on financial stress prediction. The analysis included the application of prohit, logit and multiple discriminant analysis to prediction models found in previous literature, and also involved separate samples for both bankrupt and prohlem-status companies. Finally, the statistical techniques were evaluated under extreme conditions of nonnormality.Two basic procedures were used to modify the ratio distdhutions to achieve normality. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
2
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 17 publications
2
24
2
2
Order By: Relevance
“…It seems that strong deviations from normality of data are influencing the estimation procedure of logistic regression and are affecting the classification accuracy of logistic functions. This result is consistent with some other prior studies (Hopwood et al, 1988;Silva et al, 2002). Therefore, it cannot be concluded that logistic regression is superior for model building in contrast to discriminant analysis, which is in congruence with several findings from previous research (Casey and Moreover, the unequal distribution between bankrupt and non-bankrupt firms seems to influence the classification results of both models.…”
Section: Testing Models' Assumptionssupporting
confidence: 83%
See 1 more Smart Citation
“…It seems that strong deviations from normality of data are influencing the estimation procedure of logistic regression and are affecting the classification accuracy of logistic functions. This result is consistent with some other prior studies (Hopwood et al, 1988;Silva et al, 2002). Therefore, it cannot be concluded that logistic regression is superior for model building in contrast to discriminant analysis, which is in congruence with several findings from previous research (Casey and Moreover, the unequal distribution between bankrupt and non-bankrupt firms seems to influence the classification results of both models.…”
Section: Testing Models' Assumptionssupporting
confidence: 83%
“…Especially for discriminant analysis it seems to be relevant that normally distributed data is available, because this is a theoretical pre-condition for proper application of this method (Klecka, 1980, p. 61;Hopwood, McKeown and Mutchler, 1988;Subhash, 1996, p. 263). Nevertheless, several results provided evidence that a weak violation of normality assumptions is not affecting the prediction accuracy of the final model that much, so that some departures can be argued (Hopwood et al, 1988;Silva, Stam and Neter, 2002). In some cases departures are beneficial for better discrimination in means, which can lead to better classification results compared to logistic regression (Pohar, Blas and Turk, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…This aspect is necessary, because one important pre-condition for the correct application of multivariate linear discriminant analysis is the availability of normally distributed data (Klecka, 1980, p. 61;Subhash, 1996, p. 263;Hopwood et al, 1988a). Nevertheless, a small deviation from normality can be accepted as this aspect does not infl uence the classifi cation accuracy of the forecasting models all that heavily (Hopwood et al, 1988a;Feldesman, 2002;Silva et al, 2002). Based on the results shown in the Figures 6 and 7 in the appendix, it can be seen that for almost all accounting ratios and trends, the assumption of normality cannot be presumed.…”
Section: Descriptive Statistics and Test For Normal Distributionmentioning
confidence: 99%
“…This is due to the fact that, the higher probability of bankruptcy, the higher the need of the auditors to issue going-concern opinion. Regardless of whatever bankruptcy model being employed in prior researches (Hopwood, McKeown & Mutchler, 1989;Vanstraelen, 2000) in going concern opinion, the results suggest that auditors do assess distress condition of their clients. Prior research in Malaysia by Md.…”
Section: Probability Of Bankruptcymentioning
confidence: 91%